Comparative astigmatic accuracy and optical quality of SMILE, FS-LASIK, and TICL in mild-to-moderate myopia with ≥1.00 D astigmatism - Huang, Na; Yang, Wanju; Wang, Qifeng; Zhang, Qingsong; Yang, Yanning (Frontiers in Medicine, 2025)
PurposeConsidering the unresolved trade-offs between astigmatic precision and optical quality in mild-to-moderate myopia with ≥1.0 D astigmatism, this study compares astigmatic correction accuracy and higher-order aberrations (HOAs) among three methods: small incision lenticule extraction (SMILE), femtosecond laser-assisted in situ keratomileusis (FS-LASIK), and toric implantable collamer lens (TICL) implantation.MethodsThis retrospective, non-randomized comparative study enrolled 159 eyes of 159 patients. Study participants underwent either SMILE (n = 51 eyes), FS-LASIK (n = 53 eyes), or TICL implantation (n = 55 eyes), and their visual acuity, refractive outcomes, and optical quality parameters were assessed preoperatively and at 3 months postoperatively. Astigmatic correction efficacy was evaluated using Alpins vector analysis, with results stratified by preoperative cylinder axes.ResultsAt 3 months, the residual cylinder value was significantly lower in the SMILE (−0.21 ± 0.25 D) and FS-LASIK (−0.30 ± 0.23 D) groups than in the TICL group (−0.50 ± 0.26 D) (p < 0.05). Vector analysis demonstrated comparable target-induced astigmatism across groups. However, the TICL group exhibited significantly higher difference vectors, absolute angles of error, and index of success values than both the SMILE and FS-LASIK groups. Conversely, patients who received TICL presented lower surgically induced astigmatism, correction index, and magnitude of error values than those who received SMILE and FS-LASIK. Specifically, for against-the-rule and oblique astigmatism, the surgically induced astigmatism, magnitude of error, and correction index values were significantly higher in the SMILE and FS-LASIK groups than in the TICL group. Optical quality assessment revealed that TICL induced significantly fewer total HOAs, total coma, vertical coma, and spherical aberrations than both SMILE and FS-LASIK at 3 months.ConclusionSMILE, FS-LASIK, and TICL implantation are all effective for correcting mild-to-moderate myopia with ≥1.0 D astigmatism. SMILE led to superior astigmatic correction accuracy compared with TICL and showed better astigmatic correction than FS-LASIK in this cohort. Meanwhile, TICL implantation induced significantly fewer HOAs than both SMILE and FS-LASIK, resulting in superior postoperative optical quality.